Analisis Faktor – Faktor Yang Mempengaruhi Pendapatan Nelayan Juragan Tangkapan Ikan Teri (Studi Kasus : Kelurahan Belawan Bahari Kecamatan Medan Belawan Kota Medan) - Stefanus Lugu; Mitra Musika Lubis; Rahma Sari Siregar (Jurnal Agriuma, 2019)
This study aims to determine the income level of fishermen anchovy catchers and analyze the factors that influence it. The research was conducted by purposive sampling method. The result showed that : Production Cost Variables had a negative and insignificant effect on the income of skipper fishermen, this was due to diminshing returns. Variable Amount of Labor has a positive and significant effect on the income of skipper fishermen, this is because if the greater the amount of work, the speed in obtaining the catch  (production) is more effective. Variety of Sea Trips has a positieve and significant effect on the income of fishermen, this is because if the distance goes to sea, then the amount of income of fishermen’s fishers increases. Variable Experience of skipper fishermen income, this is because if the longer or more business experience, then in managing business capital in obtaining results better and more accurate, so that income is maximized. Variable Production Costs, Number of Workers, Mileage, and Business Experience together influence the income variable.